Peer Teaching in an Interprofessional Education Activity Focused on Professional Skills Development - Tracey DelNero; Deepti Vyas (MDPI AG, 2021)
The purpose of this study was to assess the impact of a peer-taught interprofessional education (IPE) activity on pharmacy and physician assistant (PA) student self-assessed confidence and attitudes related to professional skills. First-year pharmacy (n = 210) and PA (n = 45) students participated in a two-hour IPE activity. Forty-five teams consisting of one PA and at least four pharmacy students completed three peer-teaching stations focused on diabetes device education, pulmonary device teaching/case workup, and physical assessment skills. Students completed a pre- and post-activity confidence survey and a post-activity attitudes survey. For pharmacy students, highest confidence gains were noted on the items related to performing a physical exam. For PA students, largest gains were noted on the items related to insulin delivery systems. Eighty-three percent of students either agreed or strongly agreed with the statement "I learned things during this IPE activity that I will implement in clinical practice." Seventy six percent of students felt that the physical assessment station was "beneficial or very beneficial" to their learning. A vast majority of students noted the IPE activity "somewhat or definitely" enhanced their communication with other health professionals and promoted a climate of mutual respect. In conclusion, peer teaching improved student attitudes and confidence.